2019
DOI: 10.1039/c8ta10168j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing electron transport via graphene quantum dot/SnO2 composites for efficient and durable flexible perovskite photovoltaics

Abstract: Low-temperature processed GQDs and SnO2 nanoparticles composites (G@SnO2) have been prepared through a facile synthetic path. Facilitated electron transfer and suppressed interfacial charge recombination enable flexible perovskite solar cells with superb efficiency and excellent durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 81 publications
4
70
0
Order By: Relevance
“…The excessive annealing temperature may lead to oxygen defects, which acted as unfavorable electron trap centers and thereby reduced device performance. Analogously, charge transport properties of SnO 2 electron transporting layers decorated different size of graphene quantum dots have been detected by C‐AFM . It is evident that the conductivity of SnO 2 films can be improved by doping quantum dots with suitable size.…”
Section: Applications Of C‐afm Techniquementioning
confidence: 82%
“…The excessive annealing temperature may lead to oxygen defects, which acted as unfavorable electron trap centers and thereby reduced device performance. Analogously, charge transport properties of SnO 2 electron transporting layers decorated different size of graphene quantum dots have been detected by C‐AFM . It is evident that the conductivity of SnO 2 films can be improved by doping quantum dots with suitable size.…”
Section: Applications Of C‐afm Techniquementioning
confidence: 82%
“…To truly investigate the effect of the formed permanent dipole on the surface WF of the ZnO layer, ultraviolet photoelectron spectra (UPS) spectra of ZnO and ZnO–ATAA were measured and are plotted in Figure b, showing that the WF is lowered by about 0.28 eV and the surface highest occupied molecular orbital (HOMO) level changes by about 0.21 eV with the incorporation of the ATAA layer, as expected. Figure c shows the energy levels of each layer in the PSCs, demonstrating that the energy levels of ZnO–ATAA match better with the perovskite layer due to the upshifted conduction band and WF, which contributes to the reduced interface electron transport barrier and better electron extraction from the perovskite layer …”
Section: Resultsmentioning
confidence: 99%
“…Podzorov et al have shown that step edges of rubrene 3 can be functionalized with tridecafluoro‐1,1,2,2‐tetrahydrooctyl)trichlorosilane . Surface defects and even mechanical stress are of general relevance and must definitively be taken into account to explain charge transport, at fundamental level …”
Section: Charge Transportmentioning
confidence: 99%